Inheritance of bacterial wilt resistance and performance of horticultural traits in bell pepper (Capsicum annuum var. grossum) - DEVI, JYOTI; SOOD, SONIA; VIDYASAGAR, VIDYASAGAR; SINGH, YUDHVIR (The Indian Journal of Agricultural Sciences, 2015)
The genetic nature of bacterial wilt resistance was studied in bell pepper (Capsicum annuum L. var. grossum Sendt.) plants using the P1, P2, F1, F2 and backcross generations obtained from four crosses between four parental lines, viz, EC 464107, EC 464115, Kandaghat Selection and Sweet Happy I considered as standards for resistance and/or susceptibility. The evaluation trial was conducted in bacterial wilt sick plots along with two susceptible checks, namely Indira (Hybrid) and California Wonder (Open-pollinated variety) that were included after every 15th row to ensure uniform distribution of inoculum in the experimental fields. Simultaneously, in a separate block, the parents and their F1’s were also evaluated for twelve different horticultural traits. The findings revealed that bacterial wilt resistance was governed by a single dominant gene in the cross EC 464107 × Sweet Happy I, whereas two genes with dominant and recessive epistasis dictated resistance in the crosses EC 464107 × Kandaghat Selection and EC 464115 × Kandaghat Selection, respectively. Based upon the mean performance, the hybrid EC 464107 × Kandaghat Selection was the best in terms of total and marketable fruit yield, fruits per plant and fruit length, which underscores its importance to be exploited, especially during wet season. In addition, the resistant parents EC 464107 and EC 464115 can be used to develop bacterial wilt resistant F1 hybrids as they expressed complete or near complete dominance for resistance in combination with the moderately resistant and susceptible varieties Kandaghat Selection and Sweet Happy I. Backcrossing with commercial cultivars and recombinant breeding accompanied by selection would also help to evolve bacterial wilt disease resistant, high yielding and horticulturally desirable pure line varieties.